Trade Diversification, Income, and Growth: What Do We Know? - Olivier Cadot; Céline Carrère; Vanessa Strauss-Kahn (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
This paper surveys the empirical literature on export and import diversification and its linkages with growth. We review widely-used measures of diversification and the evidence about their evolution focusing on how export diversification relates to trade liberalization and economic development. We also discuss the linkages between trade diversification and productivity at the firm and industry level, highlighting new advances on the linkages between import diversification and productivity.
Keywords: F1; O11; 330